PPAR-α Agonist Fenofibrate Decreased Serum Irisin Levels in Type 2 Diabetes Patients with Hypertriglyceridemia - Xiaomeng Feng; Xia Gao; Yumei Jia; Heng Zhang; Qingrong Pan; Zhi Yao; Ning Yang; Jia Liu; Yuan Xu; Guang Wang; Xinchun Yang (PPAR Research)
Irisin is related to insulin resistance and metabolic disorders. The physiologic effects of irisin are partially mediated through peroxisome proliferator-activated receptor-α (PPAR-α). We investigated the effect of fenofibrate, a PPAR-α agonist, on serum irisin in type 2 diabetes patients with hypertriglyceridemia. This study evaluated cross-sectional and interventional studies of 25 type 2 diabetes patients with hypertriglyceridemia (group A) and 40 controls (group B). Group A was treated with fenofibrate (200 mg/day) for 8 weeks. Serum irisin and clinical characteristics were examined. Serum irisin was significantly higher in group A compared with group B (45.15±10.48 versus 35.38±9.97 ng/ml, P<0.001) and correlated with body mass index (r=0.314, P=0.011), fasting blood glucose (r=0.399, P=0.001), total cholesterol (r=0.256, P=0.040), and high-density lipoprotein cholesterol (r=0.247, P=0.047). In multiple regression analysis after controlling for confounders, only fasting blood glucose (β=5.615, P<0.001) and high-density lipoprotein cholesterol (β=19.483, P<0.001) were independently related to serum irisin. After 8 weeks of fenofibrate treatment, serum irisin significantly decreased in group A compared with baseline (45.15±10.48 versus 38.74±12.54 ng/ml, P=0.011). Conclusively, fenofibrate decreased serum irisin in type 2 diabetes patients with hypertriglyceridemia, indicating that PPAR-α agonists may protect against metabolic disorders by improving irisin resistance.